Strain improvement and statistical media optimization for enhanced erythritol production with minimal by-products from candida magnoliae mutant R23 - Savergave, Laxman S.; Gadre, Ramchandra V.; Vaidya, Bhalchandra K.; Narayanan, Karthik (Biochemical Engineering Journal, 2011)
Mutants of Candida magnoliae NCIM 3470 were generated by ultra-violet and chemical mutagenesis to enhance erythritol production. The mutants were screened for higher reductase activity on agar plates containing high concentration of glucose and 2,3,5-triphenyl tetrazolium chloride (TTC). One of the mutants named as R23 gave maximum erythritol production, 60.3 g L(-1), compared to 14 g L(-1) of the parent strain. Glucose and yeast extract were identified as critical medium components which decide the ratio of polyols produced, mainly erythritol, mannitol and glycerol. In order to enhance the production of erythritol and to minimize the production of mannitol and glycerol, a four component-five level-three response central-composite-rotatable-design (CCRD) of response surface methodology (RSM) model was used. The optimum medium composition for erythritol production was found to contain (g L(-1)) glucose 238, yeast extract 9.2, KH(2)PO(4), 5.16 and MgSO(4) 0.23. Moreover, erythritol production was studied in a 10 L fermentor in batch and fed-batch mode using RSM optimized medium. In fed-batch fermentation, 87.8 g L(-1) erythritol was produced with 31.1% yield, without formation of any other polyols. Thus present study involving strain improvement followed by media and process optimization resulted in 6.2-fold increase in erythritol production and 3.4-fold increase in the yield. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Candida magnoliae; Erythritol; Fermentation; Metabolite over-production; Modelling; Optimization

Two-stage fermentation process for enhanced mannitol production using Candida magnoliae mutant R9 - Savergave, Laxman S.; Gadre, Ramchandra V.; Vaidya, Bhalchandra K.; Jogdand, Vitthal V. (Bioprocess and Biosystems Engineering, 2013)
Mutants of Candida magnoliae NCIM 3470 were generated by treatment of ultra-violet radiations, ethyl methyl sulphonate and N-methyl-N'-nitro-N-nitrosoguanidine. Mutants with higher reductase activity were screened by means of 2,3,5-triphenyl tetrazolium chloride agar plate assay. Among the screened mutants, the mutant R9 produced maximum mannitol (i.e. 46 g l(-1)) in liquid fermentation medium containing 250 g l(-1) glucose and hence was selected for further experiments. Preliminary optimization studies were carried out on shake-flask level which increased the mannitol production to 60 g l(-1) in liquid fermentation medium containing 300 g l(-1) glucose. A two-stage fermentation process comprising of growth phase and production phase was employed. During the growth phase, glucose was supplemented and aerobic conditions were maintained. Thereafter, the production phase was initiated by supplementing fructose and switching to anaerobic conditions by discontinuing aeration and decreasing the speed of agitation. The strategy of two-stage fermentation significantly enhanced the production of mannitol up to 240 g l(-1), which is the highest among all fermentative production processes and corresponds to 81 % yield and 4 g l(-1) h(-1) productivity without formation of any by-product.
Keywords: Candida magnoliae; D-Mannitol; Mutagenesis; Strain improvement; Two-stage fermentation